Achievement of Dynamic Equivalence in the Translation of Enola Holmes Movie’s Subtitle - Ummi Mukhoyyaroh; Abdurrachman Faridi (Universitas Negeri Semarang, 2023)
In translation, dynamic equivalence aims to deliver a text’s message in terms that a new recipient audience can understand. This research centered on analyzing the Indonesian translation of the movie subtitles for